Graduate employability and the career thinking of university STEMM students. Issue 6 (17th August 2020) - Bennett, Dawn; Knight, Elizabeth; Bell, Kenton
ABSTRACT: If graduates from STEMM – science, technology, engineering, mathematics and medical sciences – are to successfully navigate the labour market, they need diverse capabilities alongside self- and career awareness. The focus of this study was STEMM students' perceptions of self, career and employability. The study asked over 2, 000 commencing students to respond to an open question which asked how long they intended to work in their discipline. The findings lend weight to the use of social cognitive career theory, which emphasises that career- and study-related decision making are influenced by feedback and feed-forward mechanisms and by intra- and inter-personal, historical, and contemporaneous dimensions. The article ends with implications for higher education teachers, including the need for strategies with which to help a diverse student body create meaning from the career-related messages that abound in public discourse.